Portable photoacoustic system for noninvasive blood temperature measurement - Liu, Siyu (2020)
A miniaturized sensing system for noninvasive measurement of blood temperature with relatively deeper penetration has being long pursued with limited success. Here, we develop a novel photoacoustics based portable sensor for noninvasive monitoring of blood temperature with high accuracy, deep penetration depth and real time capability. Optical module (laser diode with collimation lens) and acoustic module (ring ultrasound transducer with an optical/acoustic transparent Polydimethylsiloxane coupling layer) of the system is integrated to a compact sensor head with a size similar to a human thumb. Main body is battery-powered to provide the laser driver, data acquisition and also signal processing. The overall system size is around 14 cm×8 cm×3 cm. Temperature calibration and measurement is demonstrated both on phantom and animal to achieve a high accuracy of 0.2 and 0.5 degree respectively, with a fast refreshing speed of 80 Hz. In the future, such developed photoacoustic temperature sensing device can potentially become a wearable patch sensor with further miniaturization of laser diode and use of MEMS-based piezoelectric micro-machined ultrasonic transducers (PMUT).